2010
DOI: 10.3109/10641960903443566
|View full text |Cite
|
Sign up to set email alerts
|

Religious and Spiritual Beliefs in Stroke Rehabilitation

Abstract: Faith could dampen Post-Stroke Depression (PSD), which may negatively influence recovery. The present pilot study is an initial examination of the role of religion and spirituality on the functional recovery after a recent stroke. Data were analyzed from 112 consecutive stroke inpatients, who underwent a 2-month standard rehabilitation program. All participants received the Royal Free Interview (RFI), a semi-structured interview for religious and spiritual beliefs, and were assessed on their mood with the Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
0
13
0
4
Order By: Relevance
“…Giaquinto et al reported that the strength of religious beliefs was a protective factor against emotional distress after stroke [38]. Researchers are increasingly interested in the role of religion on patient well-being [39][40][41][42]; for PSD specifically, further studies on a larger scale are needed to assess the impact of religion on patient evolution [41]. Nearly 80% of patients reported using alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Giaquinto et al reported that the strength of religious beliefs was a protective factor against emotional distress after stroke [38]. Researchers are increasingly interested in the role of religion on patient well-being [39][40][41][42]; for PSD specifically, further studies on a larger scale are needed to assess the impact of religion on patient evolution [41]. Nearly 80% of patients reported using alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…[15, 16, 32] A possible explanation for the limited interest in this topic in the cardiology literature is that spirituality is an elusive concept, encompassing both subjective dimensions that are difficult to define and operationalize, and more easily measurable, objective dimensions such as frequency of spiritual activities or spiritual/religious affiliation. [33]…”
Section: Discussionmentioning
confidence: 99%
“…Embora os alcances religiosos e espirituais sejam condições pouco exploradas na área da saúde, estudos despontam por tal temática, todavia, no que é de conhecimento dos autores, trabalhos com agrupamentos em hemiparéticos em centros de reabilitação ainda são escassos 22,23 .…”
Section: Discussionunclassified